Effect of Warm Acupuncture Combined with Bone Marrow Mesenchymal Stem Cells Transplantation on Cartilage Tissue in Rabbit Knee Osteoarthritis. (11th August 2021) - Liu, Jun-wei; Wu, Yong-li; Wei, Wei; Zhang, Yan-ling; Liu, Di; Ma, Xiao-xiu; Li, Chun; Ma, Yu-yuan
Abstract : The current study was designed to investigate the effect and underlying mechanism of warm acupuncture combined with bone marrow mesenchymal stem cells (BMSC) transplantation on cartilage tissue injury in rabbit knee osteoarthritis (KOA). In the study, 50 rabbits were randomly divided into 5 groups: blank group, KOA group, warm acupuncture group, BMSCs group, and warm acupuncture combined with BMSCs group. After warm acupuncture combined with BMSCs, the Modified Lequesne MG knee joint assessment scale was used to evaluate the degree of knee joint behavior, the Taiping Peng method generally observed the histomorphology changes of KOA rabbit cartilage, and hematoxylin-eosin staining, safranin O green staining, and toluidine blue staining were conducted to evaluate the extent of cartilage tissue pathology. Furthermore, transmission electron microscopy and TUNEL staining were used to observe cell apoptosis, and immunohistochemistry and qPCR analysis were used to detect the expression of apoptosis-related proteins and mRNA. Results showed that administration of warm acupuncture combined with BMSCs recovered the joint function and significantly decreased Lequesne MG score. The degree of cartilage tissue pathological damage has been improved, cartilage ultrastructure degeneration has recovered, peripheral blood vessels have mild edema, blood supply has gradually recovered, and even small amounts of red blood cells have appeared. In addition, warm acupuncture combined with BMSCs treatment suppressed chondrocyte apoptosis in rabbits with knee osteoarthritis by reduced TUNEL-positive chondrocytes and simultaneously reversed the mRNA expression of Bax, Bcl-2, and Caspase-3. These results indicate that warm acupuncture combined with BMSCs transplantation has a potential protective effect on rabbit KOA, which may be mediated by inhibiting chondrocyte apoptosis.